Características clínicas y epidemiológicas de los pacientes mayores de 50 años con VIH/SIDA en el Hospital Regional Docente de Trujillo - Zambrano Mendoza, Zayra Jeaneth (2018)
Patients older than 50 years with a diagnosis of HIV / AIDS are a heterogeneous group with different epidemiological and clinical characteristics than the youngest ones. Objective: To establish the clinical and epidemiological characteristics of patients over 50 years with HIV / AIDS in the Regional Teaching Hospital of Trujillo. Material and method: Cross-sectional descriptive study. We worked with 127 clinical records of patients over 50 years of age with a diagnosis of HIV / AIDS in the Regional Teaching Hospital of Trujillo from 2005 to 2015. Results: 76.4% were male between 50-59 years, 63.8% had employment, 91.3% alcohol consumption, with 70.9% never using a condom, as a pattern of 100% sexual transmission, a CD4 of less than 200 cel / ml, with high viral load and clinical stage C in 72.4%, 66.1% and 61.4% respectively. Comorbidity associated with HIV / AIDS Pulmonary tuberculosis and non-associated diabetes and hypertension are the most frequent, in addition 72.2% used first line treatment. Conclusion: The profile found was a male between 50-59 years old, heterosexual, single, who did not use a condom and who acquired the infection through sexual contact; presented in a precarious immunological situation, with very high viral load, and with some disease associated with HIV presenting a comorbidities associated with HIV / AIDS